Mental health and the wish to have a child: a longitudinal, cross-cultural comparison between Germany and China - Jürgen Margraf; Kristen L. Lavallee; Xiao Chi Zhang; Jan K. Woike; Silvia Schneider (Taylor & Francis Group, 2022)
Background The desire to have children has been declining globally, especially in industrialized nations. This study examines the physical health correlates, and positive and negative mental health correlates of the wish to have a child across time and in two countries. Method Questionnaire data were obtained from large-scale university samples of 12,574 participants in Germany and China. Results The wish to have a child (child wish) is related to positive and negative mental health in China and, to a lesser degree, in Germany. Child wish is positively related to some aspects of mental and somatic health for Chinese women and men, negatively to depression for Chinese and German men and Chinese women, and positively to stress for German men, with generally small effects. Effects hold when controlling for age, partnership status, and family affluence. Most relationships were almost equal between women and men (in both China and Germany), and between countries with the exception of two different paths in each gender group. That is, having a partner is associated with a higher child wish in both Chinese and German female students. In China, older female students are more likely to want to have a child, while older female students in Germany are less likely to want to have a child. Neither partnership nor age predict child wish for the next year. Conclusion In sum, Chinese students reported feeling more positively about having children when they were happy and healthy, with the exception that highly satisfied Chinese males report lower child wish in the next year. More depressed Chinese and German men and Chinese women reported lowered child wish, and stressed German men reported more child wish. Older students reported more (Chinese) or less (German) child wish depending on country.